SYNTHESIS, CHARACTERIZATION OF Mn3O4: ADSORPTION APPLICATION AND ANTIBACTERIAL EVALUATION - Chouchaine, Amaini; Marzouk Trifi, Ikhlass; Trifi, Beyram; ghodbane, ouassim; dhaouadi, hassouna; Touati, Fathi; Amdouni, Noureddine; Kouass, Salah (Journal of the Chilean Chemical Society, 2022)
Mn3O4 were synthesized via the hydrothermal method at 200°C for 24 h, using surfactants. The resultant products were examined by powder X-ray diffraction (XRD), Raman spectroscopy, Fourier transform infrared spectroscopy (FTIR), transmission electronic microscope (TEM), UV-visible spectroscopy and BET surface area analysis. The as-prepared materials were used for the adsorption of methylene blue dye (MB). The effect of various experimental parameters (initial concentration, adsorbent dose and temperature) and optimal experimental conditions were ascertained by response surface methodology using Doehlert model. Finally, the antibacterial activity of Mn3O4 nanoparticles was tested.